(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article is about culture, communication, and in the case of second languages, about intercultural communication. In order for second language learners to acquire pragmatic competence, they need to acquire cultural understanding and communication skills.